Innovating the Future of Water at ACE19. Issue 5 (6th May 2019) - Moore, Randy
Abstract : ACE19, which will be held June 9–12 in Denver, will be the place to learn, connect, and be inspired to solve today's global water challenges. "Innovating the Future of Water" returns as this year's conference theme, with new technologies and water sector innovations highlighted throughout the conference. The Innovation Lounge in the exhibit hall will again be the focal point for exciting new technologies, ideas, and lively discussion about innovation in the water industry.